Optimization to Hydrothermal Liquefaction of Low Lipid Content Microalgae Spirulina sp. Using Response Surface Methodology - Xuan Wei; Dengfei Jie (Journal of Chemistry)
The production and nature of the biocrude obtained from Spirulina sp. by hydrothermal liquefaction (HTL) technology is focused in this investigation. Our aim is to evaluate the interaction of different factors on the bio-oil production through HTL using microalgae that contains relatively low lipid content and high protein. Optimization of three key parameters—concentration (mass of algae per mass of solvent), reaction temperature, and holding time—was carried out by response surface methodology (RSM). In this work, we used central composite design to conduct the experiment process. Graphical response surface and contour plots were used to locate the optimum point. The final results showed that the optimum concentration, temperature, and holding time were 10.5%, 357°C, and 37 min, respectively. Under the optimum conditions established, yield of the biocrude (41.6 ± 2.2%) was experimentally obtained using the fresh microalgae. This study showed the potential of bio-oil production of Spirulina sp. by HTL technology, but it still needs more improvement of the biocrude for utilization.